2017
DOI: 10.1371/journal.pone.0177862
|View full text |Cite
|
Sign up to set email alerts
|

Angelica Dahurica ethanolic extract improves impaired wound healing by activating angiogenesis in diabetes

Abstract: Abnormal angiogenesis plays an important role in impaired wound healing and development of chronic wounds in diabetes mellitus. Angelica dahurica radix is a common traditional Chinese medicine with wide spectrum medicinal effects. In this study, we analyzed the potential roles of Angelica dahurica ethanolic extract (ADEE) in correcting impaired angiogenesis and delayed wound healing in diabetes by using streptozotocin-induced diabetic rats. ADEE treatment accelerated diabetic wound healing through inducing ang… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
28
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 36 publications
(34 citation statements)
references
References 49 publications
1
28
0
1
Order By: Relevance
“…The most common complication in patients with diabetes is an altered skin wound healing process, leading to complications such as Diabetic Foot Ulcers (DFUs), which has caused major worldwide morbidity due to various clinical and socioeconomic issues [3]. Several research studies have demonstrated that wound healing is delayed by hyperglycemia during DM [46].…”
Section: Introductionmentioning
confidence: 99%
“…The most common complication in patients with diabetes is an altered skin wound healing process, leading to complications such as Diabetic Foot Ulcers (DFUs), which has caused major worldwide morbidity due to various clinical and socioeconomic issues [3]. Several research studies have demonstrated that wound healing is delayed by hyperglycemia during DM [46].…”
Section: Introductionmentioning
confidence: 99%
“…Angelica dahurica [1, 2], which is known as ‘Baizhi’ in China, is a perennial dicotyledonous herb of the family Apiaceae . It originated in Taiwan and is widely grown in Korea, China, Japan, and Russia [3]. A .…”
Section: Introductionmentioning
confidence: 99%
“…In a previous study, we found that the AKE improved diabetic complications such as diabetic retinopathy 10 . Several studies have reported that skin wound healing is impaired and delayed in hyperglycemia 4, 5, 12. However, the effect of AKE on hyperglycemia-induced impaired wound healing has not been investigated and the mechanisms underlying these effects remain unknown.…”
Section: Introductionmentioning
confidence: 95%
“…In particular, delayed wound healing is one of the most serious diabetic complications 4 . Several research studies have demonstrated that wound healing is delayed by hyperglycemia during DM 5, 6, 7…”
Section: Introductionmentioning
confidence: 99%